ALIENASI PENDHARMA WACANA DI ZAMAN MODERN - Julianingsih P L. Eka M (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
The teachings of Hinduism are the oldest teachings not only in Indonesia, but the oldest teachings in the world. Along with the changing times, from the very simple era to the modern era, which is based on the attitude of the hedonism of the people whose tendency to change their attitude from the mindset, attitudes and behavior of people who live life with dense activities until they forget time, especially experienced by the people in big cities, of course, it will create an opportunity and challenge in the process of disseminating the Dharma teachings carried out by a discourse teacher. This research technique uses interview techniques with the results of global civilization which are characterized by the presence of increasingly rapid modern technology which is always changing from time to time. To create a global understanding of Hindu teachings, of course, a discourse teacher must be able to see the opportunities and challenges faced at this time. This great opportunity possessed by a discourse scholar in the midst of advanced civilizations such as: the opportunity to deliver using a variety of media that can reach widely and cheaply, an increase in internet usage every year, and of course with the advanced situation in this industrial era will provide an opportunity for a discourse teacher for creativity in giving dharma teachings Keywords : Alienasi, Pendharma Wacana, Modern